Aetiology and outcomes of prolonged neonatal jaundice in tertiary centres: data from the China Neonatal Genome Project. Issue 1 (18th July 2022) - Xiao, Tiantian; Wang, Jin; Wang, Huijun; Mei, Hongfang; Dong, Xinran; Lu, Yulan; Cheng, Guoqiang; Wang, Laishuan; Hu, Liyuan; Lu, Wei; Ni, Qi; Li, Gang; et al.
Abstract : Objective: To investigate the distribution of aetiologies and outcomes in neonates with prolonged neonatal jaundice. Design: An observational study. Setting: Multiple tertiary centres from the China Neonatal Genome Project. Patients: Term infants with jaundice lasting more than 14 days or preterm infants with jaundice lasting more than 21 days were recruited between 1 June 2016 and 30 June 2020. Main outcome measures: Aetiology and outcomes were recorded from neonates with prolonged unconjugated hyperbilirubinaemia (PUCHB) and prolonged conjugated hyperbilirubinaemia (PCHB). Results: A total of 939 neonates were enrolled, and known aetiologies were identified in 84.1% of neonates (790 of 939). Among 411 neonates with PCHB, genetic disorders (27.2%, 112 of 411) were the leading aetiologies. There were 8 deceased neonates, 19 neonates with liver failure and 12 with neurodevelopmental delay. Among 528 neonates with PUCHB, a genetic aetiology was identified in 2 of 219 neonates (0.9%) who showed disappearance of jaundice within 4 weeks of age and in 32 of 309 neonates (10.4%) with persistent jaundice after 4 weeks of age. A total of 96 of 181 neonates (53.0%) who received genetic diagnoses had their clinical diagnosis modified as a result of the genetic diagnoses. Conclusion: Known aetiologies were identified in approximately 80% of neonates in our cohort, and their overall outcomes were favourable. Genetic aetiology should be considered a priority in neonates with PCHB or the persistence of jaundice after 4 weeks of age. Moreover, genetic data can modify the clinical diagnosis and guide disease management, potentially improving outcomes. Abstract : In a large case series, next generation sequencing identified genetic disorders in more than 80% of newborns with prolonged jaundice.